Color image encoding in DOST domain using DWT and SVD. (December 2015) - Kumar, Manoj; Agrawal, Smita
Abstract: In this paper, a new color image encoding and decoding technique based on Discrete Orthonormal Stockwell Transform (DOST) using Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD) is proposed. The images are encrypted using bands of DOST and wavelets along with singular values of wavelet subbands. We have used the number of bands of DOST, values and arrangement of some predefined parameters using singular values of all wavelet subbands and arrangement of wavelet subbands as encoding and decoding keys in all three color planes. To ensure the correct decoding of the encoded image, it is necessary to use all the keys in correct order along with their exact values. The comparison of our technique with one of the recently proposed techniques and experimental results is used to analyze the effectiveness of the proposed technique. The proposed technique can be used for transmitting a color image more securely and efficiently through both secured and unsecured communication network. Abstract : Highlights: A new color image encoding technique using DOST bands has been proposed. Singular value decomposition is applied on wavelet subbands of DOST coefficients. Correct arrangement of keys is necessary for correct decoding of encoded images. The security of encoded images is enhanced as shown in experimental results. Through proposed technique, MSE values of correctly decoded images are very low.